Contract Variation and Changed Expectations - Ilg, Michael (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2020)
The much-maligned rule in Stilk v. Myrick, in which fresh consideration is required for a contract variation to be enforceable, is giving way across many common law jurisdictions. The purpose of this article is not to defend the doctrine of consideration from its critics, but rather to suggest that its replacement, the doctrine of economic duress, is a cure that is worse than the disease. The consideration requirement has been displaced without sufficient attention to the complementary role of promissory estoppel. By consequence, the flexibility advantages offered by equity may be circumscribed by an overly permissive view of contract variation. When both contract variations and suspensions are considered, the model of economic duress is found to be morally unpersuasive and economically inefficient. This article proposes that the modernization of the law of contract variation should be based on a model of changed expectations, wherein the parties’ expectation of performance can be varied by gratuitous promises, but these gratuitous promises are revocable with reasonable notice.